1999
DOI: 10.11150/kansenshogakuzasshi1970.73.664
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dexamethasone on the Clinical Course of Bacterial Meningitis in Children

Abstract: Of pediatric patients with purulent meningitis seen at the institutions listed in the title page of this paper between 1986 and 1994, 93 patients treated with antibiotics and dexamethasone (DXM) were compared with 91 patients treated with antibiotics alone. The patients receiving antibiotics with dexamethasone achieved overall improvement in inflammatory symptoms and signs and cerebrospinal fluid findings and became afebrile significantly earlier than those receiving antibiotics alone. However, some of the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Moreover, animal and human investigations have found that the use of dexamethasone improves the BBB damage and reduces neurological complications and CSF inflammation [1,2,14,17,19,22,25,30]. According to our data, the BBB damage is intensive during purulent meningitis and it constitutes a sensitive parameter in the outcome of the disease [6,14,21,25,29,31].…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Moreover, animal and human investigations have found that the use of dexamethasone improves the BBB damage and reduces neurological complications and CSF inflammation [1,2,14,17,19,22,25,30]. According to our data, the BBB damage is intensive during purulent meningitis and it constitutes a sensitive parameter in the outcome of the disease [6,14,21,25,29,31].…”
Section: Discussionsupporting
confidence: 53%
“…The reference value of the albumin coefficient was 1.8-7.4 × 10 -3 . An albumin coefficient value less than 9 is considered normal, a value of 10-14 indicates mild BBB dysfunction, 15-30 severe BBB dysfunction, 31-100 very severe BBB dysfunction, and if it is greater than 100, it indicates complete collapse of BBB functions [25,26].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation